Old MacDonald had a ... zoo? - Trapani, Iza (Charlesbridge, 2017)
In this revision of the classic song, Farmer MacDonald finds his farm invaded by a kangaroo, an elephant, and other animals that belong to the zoo, until he rounds them up and takes them back where they belong.